Cumplimiento del objetivo de desarrollo sostenible no. 12 - producción y consumo sostenible en la ciudad de Bogotá. (2023)
This work will address the compliance, importance and implemented measures of SDG 12 – Sustainable production and consumption for the city of Bogotá with respect to the goals of the 2030 Agenda, which, at the national level, is agreed upon through CONPES 3918 of 2018, establishing thus the strategy for the implementation of the SDGs, linked in turn by local governments through development plans. The results of this research provided a comprehensive vision of the current situation of sustainable production and consumption in Bogotá, highlighting the achievements achieved and the challenges that still persist. The states of compliance with the SDG goals, currently implemented measures, environmental problems, as well as the barriers and limitations that hinder the effective implementation of sustainable policies in the city were identified, opening the way and new research routes within the framework of the SDGs and the current management of Bogotá for its compliance.